Novel AgPd hollow spheres anchored on graphene as an efficient catalyst for dehydrogenation of formic acid at room temperature. Issue 2 (14th December 2015) - Jiang, Yiqun; Fan, Xiulin; Xiao, Xuezhang; Qin, Teng; Zhang, Liuting; Jiang, Fulei; Li, Meng; Li, Shouquan; Ge, Hongwei; Chen, Lixin
Abstract : Highly dispersed AgPd hollow spheres anchored on graphene (denoted as AgPd-Hs/G) were successfully synthesized through a facile one-pot wet-chemical route for the first time. Abstract : Highly dispersed AgPd hollow spheres anchored on graphene (denoted as AgPd-Hs/G) were successfully synthesized through a facile one-pot hydrothermal route for the first time. The fabrication strategy was efficient and green by usingl -ascorbic acid (l -AA) as the reductant and trisodium citrate dihydrate as the stabilizer, without employing any seed, surfactant, organic solvent, template, stabilizing agent, or complicated apparatus. The as-synthesized AgPd-Hs/G catalyst exhibits a sphere-shaped hollow structure with an average diameter of about 18 nm and a thin wall of about 5 nm. The hollow architecture with a thin wall and excellent dispersion on the graphene ensure that most of the atoms are located on the surface or sub-surface, which provides reactive catalytic sites for the dehydrogenation of formic acid. Therefore, a superior catalytic effect was achieved compared with other catalysts such as Pd/G and AgPd/C. The as-synthesized AgPd-Hs/G exhibits a catalytic activity with an initial turnover frequency (TOF) value as high as 333 mol H2 mol −1 catalyst h −1 even at room temperature (25 °C) toward the decomposition of formic acid. The present AgPd-Hs/G with efficient catalysis on the dehydrogenation of formic acid without any CO generation at room temperature can pave the way for a practical liquid hydrogen storage system and therefore promote the application of formic acid in fuel cell systems.